2017
DOI: 10.1037/apl0000241
|View full text |Cite
|
Sign up to set email alerts
|

Leadership training design, delivery, and implementation: A meta-analysis.

Abstract: Recent estimates suggest that although a majority of funds in organizational training budgets tend to be allocated to leadership training (Ho, 2016; O'Leonard, 2014), only a small minority of organizations believe their leadership training programs are highly effective (Schwartz, Bersin, & Pelster, 2014), calling into question the effectiveness of current leadership development initiatives. To help address this issue, this meta-analysis estimates the extent to which leadership training is effective and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
406
1
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(442 citation statements)
references
References 235 publications
(173 reference statements)
16
406
1
19
Order By: Relevance
“…The benefits of this decision are supported by research. In a recent meta‐analysis, Lacerenza, Reyes, Marlow, Joseph, and Salas (, p. 18) reported that:
… leadership training programs evaluated by a team of academics and practitioners exhibited significantly greater learning and transfer outcomes compared to those evaluated by academics or industry experts only. This finding supports the argument that the scientist–practitioner model is necessary for producing superior work.
…”
Section: Walking Side By Sidementioning
confidence: 99%
“…The benefits of this decision are supported by research. In a recent meta‐analysis, Lacerenza, Reyes, Marlow, Joseph, and Salas (, p. 18) reported that:
… leadership training programs evaluated by a team of academics and practitioners exhibited significantly greater learning and transfer outcomes compared to those evaluated by academics or industry experts only. This finding supports the argument that the scientist–practitioner model is necessary for producing superior work.
…”
Section: Walking Side By Sidementioning
confidence: 99%
“…Further research has suggested that leadership intervention programs should focus on knowledge and skills that can enhance leader effectiveness (Amagoh, 2009). These interventions have generally involved training in a workshop format, participation in executive coaching, or a combination of these two approaches (Kelloway and Barling, 2010;Lacerenza et al, 2017).…”
Section: Coaching-based Leadership Intervention and Its Efficacymentioning
confidence: 99%
“…Although there are good initiatives and significant investments in leadership skill development programs, organizations still believe they have not effectively trained their leaders. In fact, they continue to report a lack of leadership skills among their employees (Lacerenza et al, 2017). Research has shown that leaders need at least 3 to 6 months to develop coaching skills and feel comfortable using them (Grant, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Leaders focused on career outcomes (for themselves and others), facilitation and mentoring, and providing resources help organizations move toward future endeavors. It is necessary for leaders to continually augment their knowledge of people and tasks (Lacerenza, Reyes, Marlow, Joseph, & Salas, ). The leader's impact on human capital, especially, is key to organizational success and the ability to profoundly influence followers (Manderscheid & Ardichvili, ).…”
Section: Implications About the Future Of Leadershipmentioning
confidence: 99%